2021
DOI: 10.1186/s12891-021-04804-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of percutaneous transforaminal endoscopic decompression and short-segment fusion in the treatment of elderly degenerative lumbar scoliosis with spinal stenosis

Abstract: Background Degenerative lumbar scoliosis (DLS) combined with spinal stenosis is increasingly being diagnosed in the elderly. However, the appropriate surgical approach remains somewhat controversial. The aim of this study was to compare the results of percutaneous transforaminal endoscopic decompression (PTED) and short-segment fusion for the treatment of mild degenerative lumbar scoliosis combined with spinal stenosis in older adults over 60 years of age. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…4 , 5 Previous studies have demonstrated that PTED is an effective technique for treating DLSS. 6 , 7 Compared with traditional posterior lumbar interbody fusion, it has the advantages of less trauma and faster rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…4 , 5 Previous studies have demonstrated that PTED is an effective technique for treating DLSS. 6 , 7 Compared with traditional posterior lumbar interbody fusion, it has the advantages of less trauma and faster rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“… 20 Li and others revealed PTED as an effective supplement in elderly patients with degenerative lumbar scoliosis combined with spinal stenosis, with excellent rates of 90.0%. 21 Additionally, Cheng and others explored the application of PETD on central spinal stenosis and degenerative lumbar spondylolisthesis and revealed a satisfactory outcome at a good-to-excellent rate of 93.3%. 22 However, our groups demonstrated differences.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the development trend of endoscopic techniques in general and thoracic surgeries, the single-channel endoscopic technique was the first to become popular in spinal endoscopy with a light source, observation lens, and surgical instruments passing through the same pipeline. Although the current single-channel endoscopic spinal technique has been widely used in surgical removal of the protruding nucleus pulposus, surgical decompression of spinal stenosis, and even intervertebral fusion, [4] it is still a targeted technique with relatively limited surgical field and scope, and relatively high technical requirements for surgeons.…”
Section: Introductionmentioning
confidence: 99%